Persistent Urogenital Sinus: Diagnostic Imaging for Clinical Management. What Does the Radiologist Need to Know? - Valentini, Anna Lia; Giuliani, Michela; Gui, Benedetta; Laino, Maria Elena; Zecchi, Viola; Rodolfino, Elena; Ninivaggi, Valeria; Manzoni, Carlo; Bonomo, Lorenzo (American Journal of Perinatology, 2016)
Background Persistent urogenital sinus (PUGS) is a congenital pathological condition characterized by an abnormal communication between the urethra and vagina. It may be a part of a complex syndrome and can be more often associated with congenital malformations affecting the genitourinary tract system (33%) such as intersex, rectovaginal communication, bladder agenesis, absence of vagina, and hydrocolpos. The correct radiological assessment of PUGS is especially useful for clinicians since the exact anatomical evaluation of this abnormality is a crucial factor for surgical planning. The imaging study modalities, which are essentially based on ultrasonography, voiding cystourethrography, and magnetic resonance imaging, could be misinterpreted if not correctly performed.Aim The aim of this article is to highlight this rare pathological condition and to help general radiologists in achieving the correct technical approach for the diagnosis. Special attention will be paid in discussing the role of different imaging modalities and their contribution to the diagnosis and clinical management of patients.
Keywords: magnetic resonance imaging; ultrasound; urogenital sinus; voiding cystourethrography